La doctrina de la libertad en el pensamiento ácrata: de Manuel González Prada y Manuel y Delfín Lévano a Avram Noam Chomsky - Silva Montellanos, Leonel Patricio (2018)
Analyses, under the analytical methodology-hermeneutic, the contributions of Manuel González Prada and Manuel and Delfin Lévano, exponents of the Peruvian libertarian thought of the beginnings of the twentieth century and confronts them with those of Noam Chomsky. He proposes that the anarchist discourse is legitimized as a radical critique of the prevailing political systems in the West (monarchy, dictatorship, Democratic Republic) since the mid-nineteenth century, after the shortcomings of these systems of government were found to Solve economic and social problems. The discourse anarchist emerges as the confluence of liberalism and socialism, and as a corpus theoretical is in force and can be considered as a philosophy or worldview with ontological implications, axiological, ethics, Gnoseológicas.